1983
DOI: 10.2466/pr0.1983.53.3.723
|View full text |Cite
|
Sign up to set email alerts
|

The Carleton University Responsiveness to Suggestion Scale: Relationship with other Measures of Hypnotic Susceptibility, Expectancies, and Absorption

Abstract: The Carleton University Responsiveness to Suggestion Scale (CURSS) yields scores on three suggestibility dimensions. Objective (CURSS:0) scores and subjective (CURSS:S) scores reflect overt and experiential response to suggestion, respectively. Objective-Involuntariness (CURSS:OI) scores indicate the number of objective responses rated as feeling involuntary. Study 1 indicated that all three suggestibility dimensions correlated significantly with the Harvard Group Scale of Hypnotic Susceptibility, and Study 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…Suggestibility is assessed as the sum of these ratings. A test-retest reliability of .67 has been reported for the C U B S (Spanos, Radtke, Hodgins, Bertrand, Stam, & Dubreuil, 1983), and validity has been established through high correlations with other measures of suggestibility (Spanos, Radtke, Hodgins, Bertrand, Stam, & Moretti, 1983). In our sample, the internal reliabdity of objective scores, as measured by Cronbach's alpha, was .68 for both versions of the scale combined.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Suggestibility is assessed as the sum of these ratings. A test-retest reliability of .67 has been reported for the C U B S (Spanos, Radtke, Hodgins, Bertrand, Stam, & Dubreuil, 1983), and validity has been established through high correlations with other measures of suggestibility (Spanos, Radtke, Hodgins, Bertrand, Stam, & Moretti, 1983). In our sample, the internal reliabdity of objective scores, as measured by Cronbach's alpha, was .68 for both versions of the scale combined.…”
Section: Methodsmentioning
confidence: 97%
“…Responses indicating voluntary control were scored 1; those indicating a lack of voluntary control were scored 0. Also, as in standard involuntariness ratings of C U B S suggestions (Spanos, Radtke, Hodgins, Bertrand, Stam, & Moretti, 1983), responses that were not responded to behaviorally were scored 0. Involuntariness was scored as the sum of these ratings.…”
Section: Methodsmentioning
confidence: 99%
“…Two other studies (Diamond, Gregory, Lenny, Steadman, & Talone, 1974;Spanos, Rivers, & Gottlieb, 1978) that tested only males also found significant correlations between these variables. Finally, two studies (Spanos, Radtke, Hodgins, Bertrand, Starn, & Moretti, 1983;Yancher & Johnson, 1981) reported only the combined data for males and females. Both studies found significant correlations between attitudes and hypnotic responsiveness.…”
mentioning
confidence: 97%
“…However, Spanos and colleagues (1983a) used Shor & Orne's original HGSHS: A outcome measure and did not assess subjective or voluntary/involuntary responding on the HGSHS: A. Additionally, Spanos and colleagues (1983a) did not report pass percentages for individual suggestions. Furthermore, Spanos et al (1983a) did not test the significance of the difference in objective responding between the two scales. The study's ability to speak to the subjective experiences of participants and to the relative difficulty of the two scales is limited.…”
Section: Introductionmentioning
confidence: 95%